对由轴弹性变形产生回差的研究 - 徐辅仁 (Jixie chuandong)
For the double-acting accurate gearing trains, the shafting elastic deformation is also one of main factors affecting the return stagnant angle. Because the present calculating method only involves the effect of the shafting elastic torsional deformation on the return stagnant angle caused by the shafting elastic deformation, there is a relative great error in the calculating result. Through the systematic analyses and calculations, the author has derived new formulas for calculating the return stagnant angle caused by the shafting elastic deformation, which includes the effects of not only the shafting elastic torsional deformation but also the elastic bending deformation. It has been proved that the effect of the shafting elastic bending deformation on the return stagnant angle caused by the shafting elastic deformation should not be negligible.